Práticas afrorreferenciadas na pesquisa em terapia ocupacional: experiência formativa como produção de cuidado e de conhecimento engajados - Cardoso, Thainara Jardim (Universidade Federal de São Carlos, 2025)
This article aims to present and reflect on the experience of an occupational therapy student in the role of a research assistant in a doctoral study that investigates care processes with Black and Brown people through Black dances in interface with occupational therapy. The methodology consisted of a reflexive case study, based on the thematic analysis of field diaries and records of her experience during the fieldwork, which included conducting workshops with Black youth in Campinas-SP and participation in a focus group held to debate the preliminary analyses of the research, all from the perspective of Afro-referenced occupational therapy. The results highlight the centrality of the experience for professional training, as it contributed to the development of a clinical reasoning sensitive to Afro-referenced practices, in addition to skills in group facilitation. The study reinforces the role of the research assistant as a constitutive and transformative element, demonstrating how the experience proved to be a powerful tool for the production of care and knowledge. Finally, identity and belonging are emphasized as fundamental axes for connection and care, revealed through contact with different ways of doing and living occupational therapy
Afro-referenced practices in occupational therapy research: formative experience as engaged production of care and knowledge
Keywords: Pesquisa qualitativa; Saúde da população negra; Dança; Terapia Ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável; 4. Educação de Qualidade